Avocado Marketing in Colombia (2023)
A review of avocado exports and prices in Colombia was carried out, in relation to free trade agreements with different countries and communities over time. For the statistical analysis of the monthly prices per kilo of avocado in different marketplaces in Colombia, space-time models were used, such as the mixed linear model in a period of nine years (from January 2013 to August 2022). An increase in Hass variety prices was observed, while in Papelillo and common varieties there was a reduction. It was also identified that Bogotá has the highest prices for this fruit compared to other cities.